Contribution of the Leo Kristi “Fanbase” Folk Concert Community in Ballad Music in Indonesia ( 1980-2010 ) - Samudra Eka Cipta; Linda Sunarti (International Journal of Research in Education, 2023)
This research discusses about the people's concert community of Leo Krissi in the development of ballad music in Indonesia.Leo kristi people concert has its own uniqueness which is to be a wrong fan of leo kristi who is considered royal and radical. This study uses a historical approach.Limit for this study is taken in the period 1980-2010 ).Whereas 1980 was where the period of leo kristi has started to be known by his fans.Whereas, The findings in this study are about the loyalty of the producers of leo kristi who always help in the form of materials to help the process of the development of the people's concert of leo kristi.Researchers took the final limit in 2014 which constitutes the Last of  Leo Kristi folk concert held in Surabaya with the title of the last of Leo Kristi concert i Rumput Kemesraan Konser Rakyat Leo Kristi. The conclusion is that Leo Kristi is a musician who is respected by his fans so they are willing to help develop the Leo Kristi Folk Concert.